“Рядовое” позднекочевническое погребение с нерядовым обрядом из кургана 2 группы Токовские Могилы на Правобережье Днепра - Евглевский, А.В.; Данилко, Н.М.; Куприй, С.А. (Степи Европы в эпоху средневековья, 2008)
The paper gives a detailed analysis of a burial of a female nomad of the Golden Horde time unusual by its ceremonial attributes which has been found near Tokovskoie settlement on the right bank of the Dnieper.